Carved pillars flanking the entrance of the temple - Temples of India Project Team (Jio Institute, 2024)
Staircases through the present entrance (from the south) lead to the temple complex. The stairs are flanked by pillars, one on each side, carved with purnaghata kalasha (vase of plenty) and kirtimukha (face of glory). The present floor of the temple complex is made of tight-fitted bricks.